Protein-Targeted Degradation Agents Based on Natural Products - Yan Li; Yi Jia; Xiaolin Wang; Hai Shang; Yu Tian (MDPI AG, 2022)
Natural products are an important source of drug lead compounds, and natural products with significant biological activity are constantly being discovered and used in clinical practice. At present, natural products play an important role in the targeted therapy of cancer, cardiovascular and cerebrovascular diseases, nervous system diseases, and autoimmune diseases. Meanwhile, in recent years, the rise of protein-targeted degradation technologies, such as proteolysis-targeting chimeras (PROTACs) and molecular glues, has provided a new solution for drug resistance caused by clinical molecular-targeting drugs. It is noteworthy that natural products and their derivatives, as important components of PROTACs and molecular glues, play an important role in the development of protein-targeting drugs. Hence, this review summarized the protein-targeted degradation agents based on natural products, such as PROTACs and molecular glues. More natural products with the potential to be used in the development of PROTACs and molecular glues as targeted protein degradation agents are still being investigated.